Behaviour of foamed concrete filled steel tubes (CFST) - Abdul Hamid, Hanizah; Ibrahim, Azmi; Mohd. Saman, Hamidah; Mohd. Ghazali, Aruan Effendy; Md. Zain, Mohd. Raizamzamani (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
A concrete-filled steel tube (CFST) column consists of a steel tube filled with concrete. Original reason why this CFST concept was developed was to prevent shear failure and to improve ductility of short columns. In recent years, CFSTs have become increasingly popular as structural members for buildings around the world.